The Ameliorating Effects of MSCs in Controlling Treg-mediated B-Cell Depletion by Indoleamine 2, 3-dioxygenase Induction in PBMC of SLE Patients - Prajoko, Yan Wisnu; Putra, Agung; Dirja, Bayu Tirta; Muhar, Adi Muradi; Amalina, Nur Dina (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Mesenchymal stem cells (MSCs) have potent immunosuppressive properties to control systemic lupus erythematosus (SLE) disease by releasing several anti-inflammatory molecules, particularly indoleamine 2, 3-dioxygenase (IDO), and increasing regulatory T cells (Treg) to control innate and adaptive immune cells. However, how MSCs release IDO to modulate Treg in controlling B is poorly understood. Therefore, investigating IDO, Treg, and B cells following MSC administration in SLE is needed. AIM: This study aimed to investigate the ameliorating effects of MSCs in controlling B cells mediated by an increase of IDO-induced Treg in PBMC of SLE patients. METHODS: This study used a post-test control group design. MSCs were obtained from human umbilical cord blood and characterized according to their surface antigen expression and multilineage differentiation capacities. PBMCs isolated from SLE patients were divided into five groups: Sham (placebo group), control, and three treatment groups. The treatment groups were treated by coculturing MSCs to PBMCs with a ratio of 1:10, 1:25, and 1:40 for 72 h incubation. Treg and B-cell levels were analyzed by flow cytometry with cytometric bead array (CBA) while the IDO levels were determined by ELISA. RESULTS: This study showed that the percentages of B cells decreased significantly in groups treated by dose-dependent MSCs, particularly in T1 and T2 groups followed by increased Treg cell percentages. These findings were aligned with the significant increase of the IDO levels. CONCLUSIONS: MSCs regulated B cells through an increase of IDO-induced Treg in SLE patients’ PBMC.